IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI DESA DI KANTOR KELURAHAN BENDUNG KECAMATAN KASEMEN KOTA SERANG - Sukarna, Royan Habibie; Holilah, Holilah; Hilman, Mohamad; Januriana, Andi Moch (Jurnal Abdimas Bina Bangsa, 2024)
Bendung Subdistrict Office is a subdistrict office located in Kasemen subdistrict, Serang city. This sub-district office operates in the field of community administration services, such as: Making Resident Identity Cards (KTP), making Family Cards (KK), making birth certificates and making certificates according to community requests, but as time goes by the administrative needs of the community are increasing and makes it difficult for sub-district staff in the administrative service process, this condition causes administrative services to often be late and hampered because the process is still carried out manually, thus requiring a village administration information system that can help improve effective and efficient village administration services. The aim of creating this village administration information system is to help overcome problems at the Bendung sub-district office in the process of registering population, making Resident Identity Cards, Making Family Cards, making Birth Certificates, making certificates and village inventories to be effective and efficient. The methods used in this activity include needs analysis, system design, implementation, and user training. The results of this activity show that the implemented information system has succeeded in increasing the speed and accuracy of administrative data processing and facilitating access to information for the public. With this information system, it is hoped that administrative services to the community will be more optimal